HTLV-1 and HTLV-2 Infection Among Warao Indigenous Refugees in the Brazilian Amazon: Challenges for Public Health in Times of Increasing Migration - Abreu, Isabella Nogueira; Lopes, Felipe Teixeira; Lima, Carlos Neandro Cordeiro; Barbosa, Alexandre do Nascimento; Oliveira, Lehi Rodrigues de; Fujishima, Mayumi Aragão; Freitas, Felipe Bonfim; Santos, Mike Barbosa dos; Lima, Vitor Nina de; Cayres-Vallinoto, Izaura M. V.; Castelo-Branco, Socorro; Silva, Hilton P. da; et al. (Frontiers in Public Health, 2022)
Introduction: Human T-lymphotropic virus (HTLV) infection is endemic in indigenous populations of the Americas. We describe herein the prevalence of HTLV-1 and HTLV-2 infection among Warao indigenous refugees from Venezuela living in Belém, Pará, Brazil. Methods: In total, 101 individuals of both sexes (43 men and 58 women) between 18 and 77 years of age were investigated. Blood samples were collected and separated into plasma and leukocytes. Serological screening was performed using an enzyme-linked immunosorbent assay (ELISA; Murex HTLV-I+II, DiaSorin, Dartford, UK), and seropositive samples were submitted to proviral DNA extraction followed by real-time polymerase chain reaction (qPCR). A nested PCR of the env region (630 bp) followed by enzymatic digestion with XhoI was performed to identify the molecular subtype of HTLV-2, in addition to sequencing analysis of the 5'LTR-I and 5'-LTR-II regions. Results: Of the 101 individuals analyzed, 3 (3.0%) were seropositive. Molecular analysis of the pol and tax genes confirmed the HTLV-1 infection in a 55-year-old woman and HTLV-2 infection in a man (68 years old) and a woman (23 years old). HTLV-2 strains were defined by enzymatic digestion as belonging to the HTLV-2b subtype. The sequencing of the 5’LTR regions confirmed the presence of subtype 2b and identified HTLV-1 as belonging to subtype 1A (Cosmopolitan) and the Transcontinental subgroup. Among the infected patients, it was possible to conduct medical interviews with two individuals after delivery of the result. One patient with HTLV-2 reported symptoms such as joint pain, foot swelling, frequent headache, dizziness and lower back pain. The HTLV-1-positive woman was diagnosed with a tumor, dementia, urinary incontinence, felt body pain, and had spots on her body. The presence of the HTLV-2b subtype highlights the prevalence of this molecular variant among indigenous South Americans, as well as the presence of HTLV-1 Transcontinental, which has a worldwide distribution. Conclusion: These results reveal a high prevalence of HTLV-1/2 infection among Warao immigrants, suggesting migratory flow as a virus spread mechanism among human populations and alert public authorities to the need to create epidemiological surveillance programs, public social and health policies aimed at welcoming immigrants in the Brazilian territory.